2020
DOI: 10.1101/2020.08.18.256578
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NVX-CoV2373 vaccine protects cynomolgus macaque upper and lower airways against SARS-CoV-2 challenge

Abstract: There is an urgent need for a safe and protective vaccine to control the global spread of SARS-CoV-2 and prevent COVID-19. Here, we report the immunogenicity and protective efficacy of a SARS-CoV-2 subunit vaccine (NVX-CoV2373) produced from the full-length SARS-CoV-2 spike (S) glycoprotein stabilized in the prefusion conformation. Cynomolgus macaques (Macaca fascicularis) immunized with NVX-CoV2373 and the saponin-based Matrix-M adjuvant induced anti-S antibody that was neutralizing and blocked binding to the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
115
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(120 citation statements)
references
References 13 publications
(6 reference statements)
4
115
0
1
Order By: Relevance
“…Novavax has tested their recombinant spike protein based vaccine (Figure 3e) with Matrix-M adjuvant in cynomolgus macaques in three different doses (2.5 ug, 5 ug and 25 ug) in a 3 week prime boost interval via the intramuscular route (Table 1) 82,83 . Animals were then challenged on day 37 with 10 4 TCID of virus in/it.…”
Section: Results From Nhpsmentioning
confidence: 99%
“…Novavax has tested their recombinant spike protein based vaccine (Figure 3e) with Matrix-M adjuvant in cynomolgus macaques in three different doses (2.5 ug, 5 ug and 25 ug) in a 3 week prime boost interval via the intramuscular route (Table 1) 82,83 . Animals were then challenged on day 37 with 10 4 TCID of virus in/it.…”
Section: Results From Nhpsmentioning
confidence: 99%
“…Our results also demonstrated that the neutralizing titre elicited by S-2P is higher than S-WT with partial furin cleavage. This S-2P design has been adopted in other cases of the vaccine development including NVX-CoV2373 [52] and mRNA-1273 [53] that are in clinical trials. Whether the high neutralization titre by the recombinant S-2P proteins based on BEVS could translate into spectacular efficacy against COVID-19 and even SARS-CoV-2 infection remains to be determined in animal models, such as hACE2 transgenic mouse [54], hamsters [55], and monkeys [19].…”
Section: Discussionmentioning
confidence: 99%
“…To increase immunogenicity, the saponin-based adjuvant Matrix-M is included in the vaccine; spike protein subunit and adjuvant are mixed prior to injection [ 59 ]. NVX-CoV2373 was first tested in macaques ( Macaca fascicularis ) that were immunized with the vaccine and challenged with the native virus intranasally and intratracheally [ 60 ]. The monkeys were protected against COVID-19 and did not exhibit any symptoms of upper or lower airway infection or pulmonary disease.…”
Section: Current Status Of Vaccine Developmentmentioning
confidence: 99%